Effects of limestone powders on pore structure and physiological characteristics of planting concrete with sulfoaluminate cement. (20th February 2018) - Gong, Chenchen; Zhou, Xiangming; Ji, Lei; Dai, Wenyan; Lu, Lingchao; Cheng, Xin
Highlights: The 28 d PH decreased because limestone reacted with CH from clinker hydration. Limestone powders contributed to the increase of fluidity of planting materials. Root length and leaf relative water content in concrete with limestone were higher. Abstract: Limestone powders generated during the production of machine-made sands were widely used as supplementary cementitious material in making concrete, which affected concrete properties. In this paper limestone powders were added to prepare low-alkali planting cementitious material. Its alkalinity, compressive strength and fluidity were investigated to evaluate their suitability for planting concrete. Water permeability coefficient of planting concrete was investigated to make clear pore connectivity. The physiological characteristics, such as root length and relative water content of leaves, of plants grown in the planting concretes were analyzed to investigate their effects on plant growth. The results indicated that limestone powders had no effect on the alkalinity of PCMs at the early hydration ages of 1 d and 3 d. But the 28 d alkalinity of PCM with 20 wt% limestone powder decreased to 9.67 because they reacted with CH from clinker hydration and anhydrite. Adding of limestone powders into PCMs contributed to the increase of fluidity of PCMs, but too high fluidity caused that the pores in the bottom of concrete were blocked and water permeability coefficient was decreased. The water permeability coefficient of concrete with 20 wt% limestone powders was the highest of 17.9 mm/s. At 20 d after sprouting root length and relative water content of leaves of plants in concrete with 20 wt% limestone powders were 11.8% and 3.2%, respectively, higher than that in concrete without limestone powders. But much more than 20 wt% limestone powders caused too high fluidity and holes at the bottom of planting concrete blocked, such as concrete with 30 wt% limestone powders, so most plants died in it.